Perception on inter-religious interaction among Muslim and Non-Muslim: a case study in Kedah and Selangor - Jaffary Awang,; Muhammad Nazmi Abd Halim,; Muhammad Razak Idris, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Perception is one of the substantial elements that shapes the way an individual understands realities and interacts them. In Malaysia, perception either it is positive or negative, is observed as one the main factors that influence the ways their multi-ethnics societies interact to each other. This article reveals the perception levels among the multi ethnics and religious communities on the issue of inter religious relationship in the states of Kedah and Selangor, Malaysia. The findings are based on the quantitative research conducted that involves 555 respondents selected from the different religious domains i.e Islam represents the Muslim community meanwhile Buddhism, Hinduism and Christianity represent the non-Muslim community. The research data analysed using descriptive statistical test which includes frequency, percentage, min and inference statistic tests like the Mann Whitney-U and Kruskal Wallis-H to explain the respondents’ background and to evaluate the perception level of Malaysia society. The study finds that the perception level among the Muslim and non-Muslim communities with regard to the subject of inter-religious relationship is high even though there is significant difference on Mann Whitney-U: (Z -8.264, p = .000). Furthermore, there is a significant difference between the ethnic composition and states that been involved which records Kruskal Wallis-H: [x2 (1, N=555) = 70.857, p=.000] and [x2 (1, N=555) = 26.229, p=.000] respectively. The finding shows that the reality inter-religious relationship among the Malaysian society today is manageable.